A population‐based study on blood lead levels in blood donors. Issue 11 (14th July 2015) - Delage, Gilles; Gingras, Suzanne; Rhainds, Marc
Abstract : BACKGROUND: Recent studies suggested that blood transfusion may represent a significant source of lead exposure in premature infants. Objectives of this study were to determine blood lead levels (BLLs) in a representative sample of blood donors and to identify risk factors associated with BLLs of 0.15 µmol/L or more. STUDY DESIGN AND METHODS: A study was conducted in 2006 to 2007 in 49 drive sites in Quebec. Individuals who qualified for blood donation were eligible to participate. Information was harvested from blood donor file and a standardized self‐administered questionnaire. Lead analysis was performed by inductively coupled plasma mass spectrometry. Data on Quebec blood donors from 2003 to 2006 (n = 320, 543) were used to establish a reference population. Geometric mean (GM) and 95% confidence interval (CI) were used to describe the results. The project was approved by an ethics committee. RESULTS: Of 6715 eligible individuals, 3490 participated (1392 women and 2098 men). Their mean age was 46.5 years. Results were weighted for region, sex, and age. The GM of BLLs was 0.082 µmol/L (95% CI, 0.027‐0.247; range, 0.011‐2.90 µmol/L). BLLs of more than 0.15 µmol/L were found in 15.5% of participants. In multivariate analysis, BLLs were mainly explained by age and sex of participants (p < 0.001). A significant association was also found between BLLs and the region of residence, education level, dwelling age, occupational and leisure activities at high risk for lead exposure, smoking, and alcohol intake (p < 0.001). CONCLUSION: BLL in blood donors is strongly explained by sex and age, a fact that can be taken into consideration when transfusing neonates.